CHARACTERISTIC AND DIRECTIONS OF DEVELOPMENT OF MANAGEMENT ACCOUNTING SYSTEMS - V. I. Osipov (Publishing House of the State University of Management, 2019)
The expanded description of domestic and foreign management accounting systems has been adduced. The historical prerequisites of their occurrence have been revealed. The advantages and disadvantages of these systems have been determined. The necessity of their further development with the aim of improving enterprise management has been substantiated. The role of modern management accounting systems in improving the efficiency of the enterprise has been disclosed. Particular attention has been paid to the introduction and further development of regulatory systems, by means of which it is supposed to be possible to solve successfully problems of strengthening of control of the expense of resources.